Evaluation and Implementation of the Epidemiological Surveillance System for Infectious Diseases at the Class I Port Health Office in Medan in 2022 in the Working Area of Kualanamu International Airport - Nofi Susanti; Liyana Simamora; Aprillia Dwi Andira; Bella Putri Erwina; Nur Ainun Sagala (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2022)
One type of disease that can become a threat to global disease is an infectious disease. The airport is one of the public places that has the risk of becoming a portal of entry for infectious diseases. Factors influencing the entry of plague cases into Indonesia are weak supervision at the country's entry points and epidemiological surveillance activities that have not been maximized. Surveillance activities are carried out during the departure and arrival of aircraft from the infected area to the entrance to the Medan Class I port health office work area. Research Objectives: to assess and evaluate an activity using an observational approach to obtain in-depth information by observing carefully and directly at the Class I Port Health Office in Medan, the working area of Kualanamu International Airport. Method: this research is a type of evaluative research that evaluates and assesses an activity system using qualitative methods to obtain information from data sources or informants regarding activities that have been carried out, in order to be able to explain the actual situation in the field. Results: The problems encountered were workers' health, data reporting and data dissemination. Epidemiological surveillance of workers' health is still lacking so that additional workers' health is needed, then reporting weekly disease data so that current disease trends can be identified, as well as dissemination to stakeholders who are competent in their fields Keyword: Airport, Evaluation,Surveillance.